2013
DOI: 10.1523/jneurosci.1182-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recalibration to Audiovisual Asynchrony

Abstract: To combine information from different sensory modalities, the brain must deal with considerable temporal uncertainty. In natural environments, an external event may produce simultaneous auditory and visual signals yet they will invariably activate the brain asynchronously due to different propagation speeds for light and sound, and different neural response latencies once the signals reach the receptors. One strategy the brain uses to deal with audiovisual timing variation is to adapt to a prevailing asynchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
271
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(322 citation statements)
references
References 20 publications
(2 reference statements)
39
271
11
1
Order By: Relevance
“…However, the results are not in immediate agreement with a recent study by Van der Burg, Alais and Cass (2013). They demonstrated a very rapid form of cross-modal adaptation, where the offset of the previous trial in a sequence of audio-visual presentations causes a negative aftereffect on the current trial.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results are not in immediate agreement with a recent study by Van der Burg, Alais and Cass (2013). They demonstrated a very rapid form of cross-modal adaptation, where the offset of the previous trial in a sequence of audio-visual presentations causes a negative aftereffect on the current trial.…”
Section: Discussioncontrasting
confidence: 99%
“…In cross-modal research (Alais, Newell, & Mamassian, 2010), previous studies using the intertrial adaptation paradigm with audiovisual stimuli have shown the aftereffects are comparable in magnitude to those obtained with prolonged exposure paradigms (Harvey et al, 2014;Van der Burg et al, 2013Wozny & Shams, 2011) and that the effects are even present and strong when participants passively perceive the audiovisual stimuli (Van der . Although an early report suggested that the magnitude plateaus after 12-20 s of adaptation (Kay & Matthews, 1972), two subsequent studies investigating the time-course of the aftereffect concluded that the aftereffect accrues rapidly in the first few minutes but does not saturate until 20-30 minutes (Regan & Tansley, 1979;Tansley & Suffield, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…This improves efficiency as no time is lost in timeconsuming adaptation periods and every trial provides data. Moreover, as recent multisensory studies of intertrial adaptation have shown in both the spatial (Wozny & Shams, 2011) and temporal (Harvey, Van der Burg, & Alais, 2014; Van der Burg et al, 2013;Van der Burg, Orchard-Mills, & Alais, 2014) domains, adaptation effects are evident after a single brief trial. This challenges the assumption in traditional adaptation studies that prolonged exposure to an adaptor is necessary to produce reliable perceptual aftereffects.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations